Peculiarity of immunocompetent cells allocation in segmental bronchus for patients with chronic ob-structive pulmonary disease - Malofiy L.S. (Морфологія, 2012)
We made complex immunehistology ex amination of local immune system of segmental bronchus for 54 patients with chronic obstructive pulmonary disease. In the article author give principles about allocation and quantitative index for immunocompetent cells. We ascert ained correlation between level of expression, stage and clinic al course of disease. Our examination demonstrated ambiguous fate for local immunity cells duri ng formation of pathogenetical aspects about chronic obstructive pulmonary disease progress. There is a pronounced disbalance of immunoregulatory index. The predominance of cytotoxic lymphocytes is observed in the foci of disregeneration processes, namely, in proliferation, hyperpla-sia, squamous metaplasia and dysp lasia of the bronchial epithelium.